Informed Consent - Fenton, S. H.; Manion, F.; Hsieh, K.; Harris, M. (Applied Clinical Informatics, 2015)
Background: Despite efforts to provide standard definitions of terms such as “medical record”, “computer-based patient record”, “electronic medical record” and “electronic health record”, the terms are still used interchangeably. Initiatives like data and information governance, research biorepositories, and learning health systems require availability and reuse of data, as well as common understandings of the scope for specific purposes. Lacking widely shared definitions, utilization of the afore-mentioned terms in research informed consent documents calls to question whether all participants in the research process — patients, information technology and regulatory staff, and the investigative team — fully understand what data and information they are asking to obtain and agreeing to share.Objectives: This descriptive study explored the terminology used in research informed consent documents when describing patient data and information, asking the question “Does the use of the term “medical record” in the context of a research informed consent document accurately represent the scope of the data involved?”Methods: Informed consent document templates found on 17 Institutional Review Board (IRB) websites with Clinical and Translational Science Awards (CTSA) were searched for terms that appeared to be describing the data resources to be accessed. The National Library of Medicine’s (NLM) Terminology Services was searched for definitions provided by key standards groups that deposit terminologies with the NLM.Discussion: The results suggest research consent documents are using outdated terms to describe patient information, health care terminology systems need to consider the context of research for use cases, and that there is significant work to be done to assure the HIPAA Omnibus Rule is applied to contemporary activities such as biorepositories and learning health systems.Conclusions: “Medical record”, a term used extensively in research informed consent documents, is ambiguous and does not serve us well in the context of contemporary information management and governance.Citation: Fenton SH, Manion F, Hsieh K, Harris M. Informed Consent: Does Anyone Really Understand What Is Contained In The Medical Record? Appl Clin Inform 2015; 6: 466–477http://dx.doi.org/10.4338/ACI-2014-09-SOA-0081
Keywords: Medical records; informed consent; information management